2012
DOI: 10.3390/rs4072057
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Species Distribution Using Niche-Based Proxies Derived from Composite Bioclimatic Variables and MODIS NDVI

Abstract: Vegetation mapping based on niche theory has proven useful in understanding the rules governing species assembly at various spatial scales. Remote-sensing derived distribution maps depicting occurrences of target species are frequently based on biophysical and biochemical properties of species. However, environmental conditions, such as climatic variables, also affect spectral signals simultaneously. Further, climatic variables are the major drivers of species distribution at macroscales. Therefore, the object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…Model accuracy was on average higher in FR than in CH, whereas the topographical and spectral ranges observed in CH were much narrower than in FR (electronic supplementary material, S1 and figures S2, S4, S5). This agrees with previous studies where accuracy of SDMs derived from satellite images increased with steepness of ecological gradients [6]. Unlike vegetation indices, we found that importance of spectral bands differed between sites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Model accuracy was on average higher in FR than in CH, whereas the topographical and spectral ranges observed in CH were much narrower than in FR (electronic supplementary material, S1 and figures S2, S4, S5). This agrees with previous studies where accuracy of SDMs derived from satellite images increased with steepness of ecological gradients [6]. Unlike vegetation indices, we found that importance of spectral bands differed between sites.…”
Section: Discussionsupporting
confidence: 92%
“…Spectral information provided by remotely sensed reflectance is influenced by phenology, variations in morphological, structural and biochemical properties of species [3], as well as by local environmental conditions (e.g. hydric stress, soil properties or productivity [4,5]) that determine species habitat suitability [6]. Nevertheless, previous attempts to predict species distributions with hyperspectral data have generated mixed results [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of variables to the model accuracy was determined according to Young et al (2011) who stated that "the higher the variable scored the percentage of contribution, the more impact that particular variable has on predicting the occurrence of the species". Considering this statement, temperature annual range (Bio7) and annual precipitation (Bio12) are the most important variables to explain the cattle tick distribution (Feilhauer et al, 2012). Thus, annual temperature range and precipitation were capable of predicting the current and future distribution of cattle ticks in the district.…”
Section: Tick Distribution Under Current and Future Climatic Conditionsmentioning
confidence: 98%
“…The "Normalized Difference Vegetation Index" (NDVI) is perhaps the most widely used proxy [24,25]. Because of the differential nature of the reflectance of vegetation in the near infrared (NIR) and red bands of the electromagnetic spectrum, this index has been used to predict species diversity [26][27][28][29], changes in species composition [30][31][32], species distribution [33,34], the measurement of net primary productivity [35,36], and the quantification of land cover changes [37,38].…”
Section: Introductionmentioning
confidence: 99%